Проблеми контролю теплових процесів згоряння - Вуйцік, Вальдемар; Готра, Зенон; Стадник, Богдан (Видавництво Національного університету «Львівська політехніка», 2001)
In this work the analysis of combustion process in energetic boilers features was carried out. The new technique of burning process control was proposed by means of optic methods. New constructions of measuring devices were elaborated. Light guide sensors and their displacement schemes were optimized. The proposed technique expediency was experimentally established.